INSPIRE: INvestigating Stellar Populations In RElics – IX. KiDS J0842 + 0059: the first fully confirmed relic beyond the local Universe - Tortora, C; Tozzi G; Agapito, G; Barbera, F La; Spiniello, C; Li R; Carlà, G; D’Ago, G; Ghose, E; Mannucci, F; Napolitano, N R; Pinna, E; et al. (Oxford University Press (OUP), 2025)
Relics are massive, compact and quiescent galaxies that assembled the majority of their stars in the early Universe and lived untouched until today, completely missing any subsequent size growth caused by mergers and interactions. They provide the unique opportunity to put constraints on the first phase of mass assembly in the Universe with the ease of being nearby. While only a few relics have been found in the local Universe, the INSPIRE project has confirmed 38 relics at higher redshifts (z ∼ 0.2–0.4), fully characterizing their integrated kinematics and stellar populations. However, given the very small sizes of these objects and the limitations imposed by the atmosphere, structural parameters inferred from ground-based optical imaging are possibly affected by systematic effects that are difficult to quantify. In this paper, we present the first high-resolution image obtained with Adaptive Optics Ks-band observations on SOUL-LUCI@LBT of one of the most extreme INSPIRE relics, KiDS J0842 + 0059 at z ∼ 0.3. We confirm the discy morphology of this galaxy (axis ratio of 0.24) and its compact nature (circularized effective radius of ∼ 1 kpc) by modelling its 2D surface brightness profile with a point-spread function-convolved Sersic ´ model. We demonstrate that the surface mass density profile of KiDS J0842 + 0059 closely resembles that of the most extreme local relic, NGC 1277, as well as of high-redshift red nuggets. We unambiguously conclude that this object is a remnant of a high-redshift compact and massive galaxy, which assembled all of its mass at z > 2, and completely missed the merger phase of the galaxy evolution at high redshift.